Development of the Ionospheric E‐Region Prompt Radio Occultation Based Electron Density (E‐PROBED) Model - Cornelius Csar Jude H. Salinas; Dong L. Wu; Nimalan Swarnalingam; Daniel Emmons; Liying Qian (Space Weather)
Abstract This work reports the development of the first version of the E‐region Prompt Radio Occultation Based Electron Density (E‐PROBED) Model. This is an empirical model of E‐region electron density (Ne) between 90 and 120 km developed using radio occultation measurements from the COSMIC‐1 mission. This first version captures more than 80% of the observed variability in monthly‐mean latitude‐local time‐altitude E‐region Ne profiles but it does not account for longitudinal variability at constant local‐time. This work also reports a validation of E‐PROBED simulations through comparisons with ionosondes and incoherent scatter radar (ISR) E‐region Ne profiles. E‐PROBED generally agrees with these ground‐based observations during day‐time. During night‐time, there is a large disparity between E‐PROBED and ISR values. Finally, this work compares E‐PROBED with E‐region Ne simulated by the International Reference Ionosphere (IRI) and the Specified Dynamics—Whole Atmosphere Community Climate Model with Ionosphere/Thermosphere eXtension (SD‐WACCM‐X). One of the main differences amongst these models is on the simulation of variabilities that cannot be attributed to photoionization. IRI barely simulates any variability not driven by photoionization. Both E‐PROBED and SD‐WACCM‐X simulates variability not driven by photoionization. Another main difference is in the absolute magnitude of night‐time E‐region Ne values. Both IRI and SD‐WACCM‐X are substantially lower than E‐PROBED. This work first concludes that E‐PROBED can conveniently provide E‐region Ne latitude—local time variabilities and structures that COSMIC‐1 observes. This work also concludes that E‐region Ne have significant non‐photoionization driven variabilities.